2001
DOI: 10.1039/b008887k
|View full text |Cite
|
Sign up to set email alerts
|

Photoreduction of carbon dioxide by hydrogen over magnesium oxide

Abstract: Magnesium oxide was found to show activity for the reduction of carbon dioxide to carbon monoxide under photoirradiation using hydrogen as a reductant. Fourier transform infrared spectroscopy was applied to a study of the reaction mechanism by detection and identiÐcation of the surface species arising during the photoreaction. The formation of surface formate ion was observed during the photoreaction. Since CO was produced from the surface formate in the presence of under irradiation, the surface formate was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(61 citation statements)
references
References 29 publications
3
55
0
3
Order By: Relevance
“…Ye and coworkers [271] demonstrated that the surface modification of TiO 2 with NaOH could greatly enhance the CO 2 adsorption, activation, thus leading to highly effective photoreduction of CO 2 into CH 4 without loading any noble metal co-catalysts. Kohno et al [272,273] reported that the photocatalytic reduction of CO 2 to CO can be achieved over MgO. However, the mechanism of the photoreduction of CO 2 on MgO cannot be explained by the conventional band theory because MgO is not a semiconductor [272].…”
Section: Increased Basic Sites For Co 2 Adsorptionmentioning
confidence: 99%
“…Ye and coworkers [271] demonstrated that the surface modification of TiO 2 with NaOH could greatly enhance the CO 2 adsorption, activation, thus leading to highly effective photoreduction of CO 2 into CH 4 without loading any noble metal co-catalysts. Kohno et al [272,273] reported that the photocatalytic reduction of CO 2 to CO can be achieved over MgO. However, the mechanism of the photoreduction of CO 2 on MgO cannot be explained by the conventional band theory because MgO is not a semiconductor [272].…”
Section: Increased Basic Sites For Co 2 Adsorptionmentioning
confidence: 99%
“…Concurrent studies using identically prepared crystals in a different cell and using ZnSe windows and an MCT detector allowed for the inspection of the crystals for the suspected reaction between MgO and CO 2 to form MgCO 3 by probing the spectra for the carbonate features, bands centered at 1660 and 1310 cm -1 (ref 23). At no time during this series of experiments were any carboncontaining features seen in any of the IR spectra.…”
Section: Methodsmentioning
confidence: 99%
“…There are manu studies that have tried to reduce CO 2 under irradiation using several photocatalysts [90][91][92][93][94][95][96][97][98]. We found that Rh/TiO 2 , MgO, ZrO 2 and Ga 2 O 3 enable the reduction of CO 2 to proceed at room temperature and ambient pressure [99][100][101][102][103][104][105][106][107][108]. Here, the detail of the photoreduction of CO 2 over MgO and ZrO 2 is described in the following sections.…”
Section: Chemical Fixation and Photocatalytic Reduction Of Carbon Diomentioning
confidence: 94%
“…MgO exhibited photocatalytic activity for the reduction of CO 2 to CO using H 2 or CH 4 as a reductant [106,107]. After 5 h of photoirradiation using CH 4 as a reductant, the amount of evolved CO reached 3.6 lmol.…”
Section: Photoreduction Of Co 2 With H 2 or Ch 4 On Mgomentioning
confidence: 99%